2020
DOI: 10.21203/rs.3.rs-74750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnosis of Coronavirus disease by measuring serum concentrations of IL-6 and blood Ferritin

Abstract: Objectives: Coronavirus disease 2019 (COVID-19) associated by infection and high death rate. The unresolved questions about the fatality rate of COVID-19 is most probably related to cytokine storm syndrome. There is currently no specific medication. Understanding the pathogenic pathway of this disease will lead to production of treatment and decreases of death rate. The aim of this study is to investigate changes of peripheral blood parameters (Interleukin-6 and Ferritin) in COVID-19 patients, which may be ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…However, the study performed on our patients indicates significantly higher concentrations of ferritin and IL-6 in patients with COVID-19 requiring intensive care comparing with those hospitalized in non-ICU departments. With our results, we confirm observations made by other groups showing that IL-6 allows distinguishing between severe and nonsevere COVID-19 [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the study performed on our patients indicates significantly higher concentrations of ferritin and IL-6 in patients with COVID-19 requiring intensive care comparing with those hospitalized in non-ICU departments. With our results, we confirm observations made by other groups showing that IL-6 allows distinguishing between severe and nonsevere COVID-19 [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the concentration of IL-6 above 24 pg/mL indicated the development of hypoxemia with a sensitivity of 100% and a specificity of 88.9% [ 38 ]. Parviz et al found that the level of IL-6, the level of ferritin, and hematological parameters including WBC and the number of lymphocytes and neutrophils had a direct positive correlation with the concentration of hemoglobin [ 39 ]. Our observations are in line with their results.…”
Section: Discussionmentioning
confidence: 99%